1974
DOI: 10.1159/000162708
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Fibrinolytic and Elastase Activity Among Clinical Isolates of <i>Serratia Marcescen</i><i>s</i>

Abstract: Thirty-three of 35 clinical isolates of Serratia marcescens examined displayed fibrinolytic activity, whereas only 5 isolates elaborated a weakly active elastase. All strains liquefied gelatin, hydrolyzed DNA, produced lipases and a lecithinase, but none revealed hyaluronidase or collagenase activity. Twenty-one, 16, and 30 of the isolates hemolyzed sheep, rabbit, and human erythrocytes, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1979
1979
1989
1989

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…As exemplified by the diverging fibrinolytic abilities of the 5 strains of S. faecalis, interstrain intraspecies variation occurred and was associated with diverging results of the gelatin liquefaction test. For S. marcescens, others have found a similar correlation between gelatin liquefac tion and fibrinolytic enzymatic activity [12], These authors suggested that the gelatinase and 'fibrinolysin' of S. marcescens possibly are the same enzyme.…”
Section: Discussionmentioning
confidence: 84%
“…As exemplified by the diverging fibrinolytic abilities of the 5 strains of S. faecalis, interstrain intraspecies variation occurred and was associated with diverging results of the gelatin liquefaction test. For S. marcescens, others have found a similar correlation between gelatin liquefac tion and fibrinolytic enzymatic activity [12], These authors suggested that the gelatinase and 'fibrinolysin' of S. marcescens possibly are the same enzyme.…”
Section: Discussionmentioning
confidence: 84%
“…Examinations of other S. marcescens strains, by four other groups of investigators, support the idea that many strains ofS. marcescens can elaborate several extracellular proteases which differ from one another with regard to their substrate specificities (49), pH optima (22), sensitivities to inactivation by EDTA and DFP (22), isoelectric points (50), and electrophoretic mobilities in agarose gel (19). Additional studies are needed to isolate, characterize, and compare the different proteases of S. marcescens.…”
Section: Resultsmentioning
confidence: 97%
“…Until recently, the haemolytic activity of Serratia marcescens strains was the subject of interest in only few papers [3][4][5]11,12]. Profound studies of this activity were performed by Braun et al [1,2,6,7] who found the lytic substance cell-bound.…”
Section: Introductionmentioning
confidence: 99%